Flow field explorations and design improvements of a hybrid rocket motor LOx feed line - Rajendran, David John; Santhanakrishnan, Mani Sekaran; Pachidis, Vassilios; Messineo, Jerome (Elsevier, 2024)
The oxidizer system in a hybrid rocket motor needs to deliver the flow from a pressurized storage tank to multiple combustor ports. Pressure losses in the oxidizer system directly impacts combustor pressure and consequently the vehicle performance. However, oxidizer feed line designs till date have been done using simple 1D tools. Higher fidelity flow analysis methods have not been reported in the literature to identify loss generating features. Therefore, a design improvement study was carried out to identify and alleviate the impact of undesirable flow features in a typical oxidizer system design. An experimentally calibrated 3D RANS approach is applied to a typical LOx feed system which includes steps, splitters, ports, and pipes with multiple bends. These design features result in varying degrees of flow separation, secondary flows and vortical flow features and result in total pressure losses of up to 7 %. This loss means that the storage tank needs to be pressurized further to accommodate such losses and ensure combustor performance. A targeted design improvement approach that features simple, alternative, implementable solutions in the loss-generating regions is discussed. The best of these design improvements can reduce the total pressure loss to 4 %, indicating a 43 % reduction in the losses and reduced impact on storage tank design and combustor performance. Therefore, this paper demonstrates that a higher fidelity design enhancement process of the oxidizer feed system, which is often neglected in such detailed studies, can result in overall vehicle level design improvements to ensure mission targets are met effectively.
Keywords: Liquid oxygen; Flow shear stress rates; Vorticity; Total pressure loss; Stream tube; Design exploration; 40 Engineering; 4001 Aerospace Engineering; Aerospace & Aeronautics